Synthesis of Isothiocineole and Application in Multigram-Scale Sulfur Ylide Mediated Asymmetric Epoxidation and Aziridination - Fearraigh, Martin P. Ó; Matlock, Johnathan V.; Illa, Ona; McGarrigle, Eoghan M.; Aggarwal, Varinder K. (Synthesis, 2018)
The synthesis of the chiral sulfide isothiocineole from limonene and elemental sulfur on multi-gram scale and its alkylation to make >50 g of the corresponding benzylsulfonium salt are described. The application of this salt to the sulfur ylide-mediated asymmetric epoxidation of aldehydes and the asymmetric aziridination of imines on a >5 g scale is demonstrated.
Keywords: sulfur ylide; asymmetric epoxidation; asymmetric aziridination; chiral sulfide